Nuclear Deterrence in the 21st Century Lessons from the Cold War for a New Era of Strategic Piracy - Delpech, Thérèse (RAND Corporation, 2012)
Deterrence remains a primary doctrine for dealing with the threat of nuclear weapons in the 21st century. The author reviews the history of nuclear deterrence and calls for a renewed intellectual effort to address the relevance of concepts such as first strike, escalation, extended deterrence, and other Cold War-era strategies in today's complex world of additional superpowers, smaller nuclear powers, and nonstate actors.